The Effect of Perceptions of Service Quality on Parents' Decisions in Making Choices at IT Rabbani Private Middle School Bengkulu City - Alvafindo Alvafindo; Khairul Bahrun (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the influence of the influence of perceived service quality on the decisions of parents in making choices at private junior high schools IT Rabbani Bengkulu City. This type of research uses a quantitative descriptive research method. The population used in this study were parents of IT Rabbani Private Middle School students, Bengkulu City. The number of respondents in this study amounted to 132 people. The data collection method uses a questionnaire and uses analytical techniques using multiple linear regression analysis tests and hypothesis testing, namely the t test and f test. Based on the results of multiple linear regression, the regression equation Y = 10.646 + 0.436X and the results of the t-test and f-test of this study can be concluded that the perception of service quality has a significant effect on student parents' decisions. 7.909 > 1.657) and (sig α = 0.03 <0.50). This means H_0 is rejected and H_a is accepted. Perceptions of Service Quality (X) have a significant direct effect on Student Parents' Decisions (Y) at Private Junior High School IT Rabbani City of Bengkulu, this is evidenced by the F test showing the value of F_count>F_table, namely (62,545 > 3.16) and (sig α = 0.000 <0.050, this means that H_0 is rejected and H_a is accepted.